Tradisi Kawin Gantung di Jawa Barat dalam Perspektif Perlindungan Hak Anak di Bawah Umur - Ilahi Datilah; Zein Bastian (Journal of Law, Society, and Islamic Civilization, 2022)
This study aims to explain about ‘kawin gantung’ in the Sundanese tribal community, especially in several areas in West Java as part of a tradition that is still being maintained by some local people. The research method used is analytical descriptive research, which is a method carried out through studying and analyzing and giving an overview of the existence of “Kawin Gantung” in several areas in West Java in perspective on the protection of minors using a qualitative approach by providing interpretation of the data obtained by looking at the rule of law, theories and principles of law with the aim of answering the problem, with data collection technique through literatur study. The findings in this study that ‘kawin gantung’ with objects of minors which are still being carried out or maintained by some people in several areas in West Java, including in Cipaeh Serdang Village, Tangerang Regency, Cikawung Village, Tasikmalaya Regency, and Ujung Gebang Village, Cirebon Regency are not in line with the provisions that regulate the minimum age limit for marriage and is not in line with the protection and respect for children's rights, especially the right to have their opinions heard and the right to obtain tion against child marriage.